The Probation System in Indonesia: Facts from the Probation Center (BAPAS) Class 1 South Jakarta - Prativi, Dhiajeng Cinthya; Meliala, Adrianus Eliasta Sembiring (Universitas Muhammadiyah Ponorogo, 2024)
The recidivism problem in Indonesia today can be associated with the existence of a work phenomenon that describes discrepancy. The discrepancy in question means the existence of a high difference or gap itself between the real form and the ideal or the expectation with the reality. One of them can occur in BAPAS which carries out the function of assisting, mentoring, and supervising Clients due post-imprisonment. Research method used is descriptive qualitative research and the data collection technique is literature study and observation in the form of interviews. The results of the research show that the facts on the ground are full of problems that seem to be without improvement. Facts found that the current training for PK tends to be only administrative, even though when carrying out their duties, soft skills are needed; besides that, BAPAS still tends to do repetition from existing programs, even though there should be a redesign program that is more adaptive and could build Client enthusiasm; and any other facts. So, this research will reveal deeper facts regarding the duties and functions of PK in BAPAS and to be aligned with the probation theory.